A hydrothermal inorganic solid electrolyte and its preparation method and application

The lithium aluminum calcium silicon inorganic solid electrolyte formed by hydrothermal method solves the problems of high cost and cumbersome processes in the existing technology, realizes the preparation of inorganic solid electrolytes with low cost and simple processes, improves electrochemical performance and stability, and has good commercial application potential.

CN119381527BActive Publication Date: 2025-04-18SOUTH CHINA UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411489054.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-04-18
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The existing inorganic solid electrolytes have high cost, cumbersome molding process, and it is difficult to meet commercial needs. In addition, traditional liquid electrolytes have safety problems and low theoretical limit energy density.

Method used

The lithium aluminum calcium silicon inorganic solid electrolyte formed by hydrothermal method has a molecular formula of LixAlyCa3 (SiO3)10. The synchronous molding of the sheet is achieved by ball milling mixing and hydrothermal synthesis, avoiding high-pressure compaction and high-temperature sintering.

Benefits of technology

It realizes low-cost inorganic solid electrolyte preparation, simplifies the process flow, improves electrochemical performance and stability, and has good commercial application potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381527B_ABST
    Figure CN119381527B_ABST
Patent Text Reader

Abstract

The present invention discloses a hydrothermal inorganic solid electrolyte and its preparation method and application. The inorganic solid electrolyte has a molecular formula of Li x Al y Ca3(SiO3) 10 ; wherein x is 8 to 11, and y is 1 to 2; the preparation method is as follows: an inorganic compound containing lithium, aluminum, calcium, and silicon elements is mixed with water and then transferred to a ball mill for ball milling to obtain a paste required for a hydrothermal reaction; the paste is then transferred to a flat-bottomed mold, the paste is evenly spread horizontally in the mold, and then placed in a saturated steam environment at 150°C to 190°C for hydrothermal synthesis and simultaneous forming of thin sheets, and finally dried to obtain the inorganic solid electrolyte. The inorganic solid electrolyte prepared in the present invention has good electrochemical properties and can be used in the fields of energy storage materials and lithium metal solid-state batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of all-solid-state batteries, and in particular to an inorganic solid electrolyte formed by a hydrothermal method, and a preparation method and application thereof. Background Art

[0002] Traditional liquid electrolyte batteries generally have certain safety issues, and their low theoretical limit energy density can no longer meet the increasingly high application requirements. Solid electrolytes are one of the core technologies of the next generation of high-performance batteries. Their high mechanical strength and stability can fundamentally solve safety issues such as battery spontaneous combustion and lithium dendrite short circuit, and are expected to increase the energy density of batteries.

[0003] At present, inorganic solid electrolytes are mainly divided into oxides, sulfides, halides and other types, which can give the battery excellent safety performance while meeting the lithium ion transmission during the battery charging and discharging process. However, the above common inorganic solid electrolytes are generally expensive. For example, expensive lithium sulfide, rare earth and other substances are required as key raw materials, and the above common solid electrolytes need to be formed before assembling the battery to form the specific thin sheets required for assembling the battery. In addition, the inorganic solid electrolyte forming process often requires cumbersome processes such as high-pressure compaction and high-temperature sintering, which is difficult to meet commercial needs.

[0004] Therefore, how to achieve inorganic solid electrolytes with good electrochemical properties at room temperature based on low-cost raw materials and simple molding processes is of great significance to the development and commercialization of inorganic solid-state electrolysis. Summary of the invention

[0005] The primary purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and provide an inorganic solid electrolyte.

[0006] Another object of the present invention is to provide a method for preparing the inorganic solid electrolyte.

[0007] Another object of the present invention is to provide an application of the inorganic solid electrolyte.

[0008] The purpose of the present invention is achieved through the following technical solutions:

[0009] An inorganic solid electrolyte with the molecular formula Li x Al y Ca3(SiO3) 10 ; Among them, x is 8~11, and y is 1~2.

[0010] The method for preparing the inorganic solid electrolyte comprises the following steps:

[0011] (1) Raw materials ball milling and mixing

[0012] The inorganic compound containing lithium, aluminum, calcium and silicon elements is mixed with water and then transferred to a ball mill for ball milling to obtain a paste required for hydrothermal reaction;

[0013] (2) Hydrothermal forming

[0014] The paste obtained in step (1) is transferred to a flat-bottomed mold, so that the paste is evenly spread horizontally in the mold, and then placed in a saturated steam environment at 150°C to 190°C for hydrothermal synthesis and simultaneous forming of thin sheets to obtain lithium aluminum calcium silicon type inorganic solid electrolyte thin sheets Li x Al y Ca3(SiO3) 10 ; Wherein, x is 8 to 11, and y is 1 to 2;

[0015] (3) Dehydration and drying

[0016] The lithium aluminum calcium silicon inorganic solid electrolyte sheet Li obtained in step (2) x Al y Ca3(SiO3) 10 The inorganic solid electrolyte is obtained by drying.

[0017] In step (1), the inorganic compound containing lithium, aluminum, calcium and silicon elements is preferably a powdered raw material (powder), including inorganic powder containing lithium, inorganic powder containing silicon, inorganic powder containing aluminum, inorganic powder containing calcium, etc. Before ball milling, the four kinds of inorganic powders can be mixed and then mixed evenly with water.

[0018] The inorganic compound containing lithium element described in step (1) is preferably lithium hydroxide.

[0019] The inorganic compound containing aluminum element in step (1) includes at least one of aluminum oxide and aluminum hydroxide.

[0020] The inorganic compound containing calcium element in step (1) includes at least one of calcium oxide and calcium hydroxide.

[0021] The inorganic compound containing silicon element described in step (1) is preferably silicon dioxide.

[0022] The mass ratio of the total mass of the inorganic compound containing lithium, aluminum, calcium and silicon elements described in step (1) to water is 1:6 to 9, preferably 1:9.

[0023] The ball mill described in step (1) is a high-energy ball mill, the ball-to-material absolute dry mass ratio is 4:1, the ball milling speed is 600-700 rpm, and the ball milling time is 12-18 h.

[0024] The molar ratio of lithium, aluminum, calcium and silicon atoms in the paste described in step (1) is 8 to 11:1 to 2:3:10.

[0025] The particle size of the paste described in step (1) is ≤200 nm.

[0026] The time of the hydrothermal synthesis in step (2) is 12 to 24 hours.

[0027] The crystal form of the lithium aluminum calcium silicon inorganic solid electrolyte sheet described in step (2) is garnet type (LLZO) and the bulk density is 2.10-2.15 g / cm 3 .

[0028] The thickness of the lithium aluminum calcium silicon inorganic solid electrolyte sheet described in step (2) is controlled by the amount of paste added, and the thickness is preferably 50 to 100 μm.

[0029] The drying conditions in step (3) are: drying at 105±5°C for 5 to 10 h; preferably: drying at 105°C for 8 h.

[0030] Application of the inorganic solid electrolyte in energy storage materials.

[0031] The energy storage materials include energy storage materials used in electric vehicles (electric cars), energy storage devices, and portable devices (portable devices such as laptop computers and smart phones).

[0032] The application of the inorganic solid electrolyte in the preparation of lithium metal solid-state batteries (solid-state lithium batteries, all-solid-state batteries).

[0033] Compared with the prior art, the present invention has the following advantages and effects:

[0034] 1. The raw materials of the lithium aluminum calcium silicon type inorganic solid electrolyte in the present invention are low in price, the preparation method is simple, efficient, green and environmentally friendly, and has the potential for large-scale commercial application.

[0035] 2. The lithium aluminum calcium silicon inorganic solid electrolyte prepared in the present invention has a garnet-type (LLZO) crystal structure. Silicon, aluminum, and calcium atoms, as important components of the solid electrolyte skeleton, construct the overall framework of the crystal, which can effectively improve the stability and interplanar spacing of the solid electrolyte.

[0036] 3. The lithium aluminum calcium silicon type inorganic solid electrolyte prepared by the present invention has a thickness of only 50-100 μm and has excellent ionic conductivity and safety performance at room temperature.

[0037] 4. The present invention adopts a hydrothermal synthesis method to prepare a lithium aluminum calcium silicon type inorganic solid electrolyte. The raw materials used are all low-cost inorganic powders containing lithium, aluminum, calcium, and silicon. In addition, the synthesis of the inorganic solid electrolyte and the simultaneous forming of its thin sheets can be achieved during the hydrothermal synthesis process, which can avoid the compaction and sintering operations of traditional inorganic solid electrolytes and can significantly reduce the production cost of the inorganic solid electrolyte.

[0038] 5. The lithium metal solid-state battery assembled using lithium aluminum calcium silicon inorganic solid electrolyte sheets in the present invention has excellent electrochemical performance, and the room temperature ionic conductivity can reach 8.0×10 -4 S / cm, and the optimal interface resistance and bulk resistance are only 177.9 Ω and 64.3 Ω, respectively. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a photograph of the lithium aluminum calcium silicon type inorganic solid electrolyte sheet prepared in Example 1 of the present invention.

[0040] Figure 2 This is a microscopic morphology of the lithium aluminum calcium silicon type inorganic solid electrolyte prepared in Example 1 of the present invention.

[0041] Figure 3 It is a graph showing the bulk resistance test and ionic conductivity test of the lithium aluminum calcium silicon type inorganic solid electrolyte prepared in Example 3 of the present invention.

[0042] Figure 4 This is a graph showing the interface resistance of the lithium aluminum calcium silicon type inorganic solid electrolyte prepared in Example 3 of the present invention.

[0043] Figure 5 This is the X-ray diffraction pattern of the lithium aluminum calcium silicon type inorganic solid electrolyte prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0044] The present invention is further described in detail below in conjunction with the examples, but the embodiments of the present invention are not limited thereto. The raw materials and reagents used in the following examples, unless otherwise specified, can be obtained from commercial sources. The experimental methods in the following examples where specific conditions are not specified are usually based on conventional conditions.

[0045] In the present invention, unless otherwise specified, all percentages (%) are mass percentages.

[0046] The lithium hydroxide involved in the examples and comparative examples of the present invention was purchased from Shanghai Bangcheng Chemical Co., Ltd., and the effective content was not less than 99.9%.

[0047] The silicon dioxide, aluminum oxide, aluminum hydroxide, calcium oxide and calcium hydroxide involved in the examples and comparative examples of the present invention are all analytically pure and purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0048] The embodiments and comparative examples of the present invention all use 0.5 mm thick lithium sheets as negative electrodes and LiFePO4 as positive electrodes to assemble lithium metal all-solid-state batteries for various electrochemical performance tests. The above positive and negative electrode materials are all commercial products purchased from Clude New Energy Technology Co., Ltd.

[0049] Example 1

[0050] (1) Raw materials ball milling and mixing

[0051] Lithium hydroxide, aluminum oxide, calcium oxide and silicon dioxide inorganic powders were mixed according to the molar ratio of Li, Al, Ca and Si atoms contained therein of 8:2:3:10, distilled water was added to make the mass ratio of solid powder to water 1:9, and the mixture was transferred to a high-energy ball mill, the ball material absolute dry mass ratio (i.e. the mass ratio of ball milling balls to solid powder, the same below) was 4:1, the ball milling speed was 600 rpm, and the time was 18 h, to obtain the paste required for the hydrothermal reaction (paste particle size ≤ 200 nm);

[0052] (2) Hydrothermal forming

[0053] The paste prepared in step (1) is transferred to a flat-bottomed mold, and the paste is evenly spread horizontally in the mold. The paste is placed in a saturated steam environment at 150°C for hydrothermal synthesis and simultaneous forming of thin sheets. The hydrothermal synthesis time is 24 h, and a dense and flat lithium aluminum calcium silicon inorganic solid electrolyte thin sheet can be obtained, and its molecular formula is Li8Al2Ca3(SiO3) 10 , the bulk density is 2.10 g / cm 3 , thickness: 100 μm;

[0054] (3) Dehydration and drying

[0055] The lithium aluminum calcium silicon inorganic solid electrolyte sheet obtained in step (2) is placed in an oven at 105° C. and dried for 8 h to obtain the hydrothermal formed inorganic solid electrolyte sheet ( Figure 1 and Figure 2 ).

[0056] Example 2

[0057] (1) Raw materials ball milling and mixing

[0058] Lithium hydroxide, aluminum hydroxide, calcium hydroxide and silicon dioxide inorganic powders were mixed according to the molar ratio of Li, Al, Ca and Si atoms contained therein of 9:1.67:3:10, distilled water was added to make the mass ratio of solid powder to water 1:9, and the mixture was transferred to a high-energy ball mill with an absolute dry mass ratio of 4:1. The ball milling speed was 650 rpm for 15 h to obtain the paste required for the hydrothermal reaction (paste particle size ≤ 200 nm);

[0059] (2) Hydrothermal forming

[0060] The paste prepared in step (1) is transferred to a flat-bottomed mold, and the paste is evenly spread horizontally in the mold. The paste is placed in a saturated steam environment at 165°C for hydrothermal synthesis and simultaneous forming of the thin sheet. The hydrothermal synthesis time is 20 h, and a dense and flat lithium aluminum calcium silicon inorganic solid electrolyte thin sheet is obtained, whose molecular formula is Li9Al 1.67 Ca3(SiO3) 10 , the bulk density is 2.12 g / cm 3 , thickness: 80 μm;

[0061] (3) Dehydration and drying

[0062] The lithium aluminum calcium silicon inorganic solid electrolyte sheet obtained in step (2) is placed in an oven at 105° C. and dried for 8 h to obtain the hydrothermally formed inorganic solid electrolyte sheet that can be used to assemble lithium metal solid-state batteries.

[0063] Example 3

[0064] (1) Raw materials ball milling and mixing

[0065] Lithium hydroxide, aluminum oxide, calcium hydroxide and silicon dioxide inorganic powders were mixed according to the molar ratio of Li, Al, Ca and Si atoms contained in them of 10:1.33:3:10, distilled water was added to make the mass ratio of solid powder to water 1:9, and the mixture was transferred to a high-energy ball mill with an absolute dry mass ratio of 4:1. The ball milling speed was 700 rpm for 12 h to obtain the paste required for the hydrothermal reaction (paste particle size ≤ 200 nm);

[0066] (2) Hydrothermal forming

[0067] The paste prepared in step (1) is transferred to a flat-bottomed mold, and the paste is evenly spread horizontally in the mold. The paste is placed in a saturated steam environment at 175°C for hydrothermal synthesis and simultaneous forming of thin sheets. The hydrothermal synthesis time is 18 h, and a dense and flat lithium aluminum calcium silicon inorganic solid electrolyte thin sheet is obtained, whose molecular formula is Li 10 Al 1.33 Ca3(SiO3) 10 , the bulk density is 2.13 g / cm 3 , thickness: 60 μm;

[0068] (3) Dehydration and drying

[0069] The lithium aluminum calcium silicon inorganic solid electrolyte sheet obtained in step (2) is placed in an oven at 105° C. and dried for 8 h to obtain the hydrothermally formed inorganic solid electrolyte sheet that can be used to assemble lithium metal solid-state batteries.

[0070] Example 4

[0071] (1) Raw materials ball milling and mixing

[0072] Lithium hydroxide, aluminum hydroxide, calcium oxide and silicon dioxide inorganic powders were mixed according to the molar ratio of Li, Al, Ca and Si atoms contained therein of 11:1:3:10, distilled water was added to make the mass ratio of solid powder to water 1:9, and the mixture was transferred to a high-energy ball mill with an absolute dry mass ratio of 4:1. The ball milling speed was 700 rpm for 12 h to obtain the paste required for the hydrothermal reaction (paste particle size ≤ 200 nm);

[0073] (2) Hydrothermal forming

[0074] The paste prepared in step (1) is transferred to a flat-bottomed mold, and the paste is evenly spread horizontally in the mold. The paste is placed in a saturated steam environment at 190°C for hydrothermal synthesis and simultaneous forming of thin sheets. The hydrothermal synthesis time is 12 h, and a dense and flat lithium aluminum calcium silicon inorganic solid electrolyte thin sheet is obtained, whose molecular formula is Li 11 Al1Ca3(SiO3) 10 , the bulk density is 2.15 g / cm 3 , thickness: 50 μm;

[0075] (3) Dehydration and drying

[0076] The lithium aluminum calcium silicon inorganic solid electrolyte sheet obtained in step (2) is placed in an oven at 105° C. and dried for 8 h to obtain the hydrothermally formed inorganic solid electrolyte sheet that can be used to assemble lithium metal solid-state batteries.

[0077] Comparative Example 1

[0078] The comparative example is a lithium calcium silicon type solid electrolyte without aluminum atoms, and the rest of the preparation process is the same as the above embodiment, and the specific steps are as follows:

[0079] (1) Raw materials ball milling and mixing

[0080] Lithium hydroxide, calcium oxide and silicon dioxide inorganic powders were mixed according to the molar ratio of Li, Ca and Si atoms contained therein of 11:3:10, distilled water was added to make the mass ratio of solid powder to water 1:9, and the mixture was transferred to a high-energy ball mill with an absolute dry mass ratio of 4:1. The ball milling speed was 700 rpm for 12 h to obtain the paste required for the hydrothermal reaction (paste particle size ≤ 200 nm);

[0081] (2) Hydrothermal forming

[0082] The paste prepared in step (1) is transferred to a flat-bottomed mold, and the paste is evenly spread horizontally in the mold. The paste is placed in a saturated steam environment at 190°C for hydrothermal synthesis and simultaneous forming of thin sheets. The hydrothermal synthesis time is 12 h, and a dense and flat lithium calcium silicon inorganic solid electrolyte thin sheet is obtained, whose molecular formula is Li 11 Ca3(SiO3) 10 , the bulk density is 2.50 g / cm 3 , thickness: 50 μm;

[0083] (3) Dehydration and drying

[0084] The lithium calcium silicon type inorganic solid electrolyte sheet obtained in step (2) is placed in an oven at 105° C. and dried for 8 h to obtain the hydrothermally formed inorganic solid electrolyte sheet that can be used to assemble lithium metal solid-state batteries.

[0085] Comparative Example 2

[0086] In this comparative example, the molar ratio of lithium, aluminum, calcium and silicon atoms is 5:3:3:10, and the rest of the preparation process is the same as that in the above embodiment, and the specific steps are as follows:

[0087] (1) Raw materials ball milling and mixing

[0088] Lithium hydroxide, aluminum hydroxide, calcium hydroxide and silicon dioxide inorganic powders were mixed according to the molar ratio of Li, Al, Ca and Si atoms contained in them of 5:3:3:10, distilled water was added to make the mass ratio of solid powder to water 1:9, and transferred to a high-energy ball mill, the ball material absolute dry mass ratio was 4:1, the ball milling speed was 700 rpm, and the time was 12 h to obtain the paste required for the hydrothermal reaction (paste particle size ≤ 200 nm);

[0089] (2) Hydrothermal forming

[0090] The paste prepared in step (1) was transferred to a flat-bottomed mold, and the paste was evenly spread horizontally in the mold. The paste was placed in a saturated steam environment at 190°C for hydrothermal synthesis. The hydrothermal synthesis time was 12 h, and the molecular formula of Li5Al3Ca3(SiO3) was obtained. 10 Inorganic powder;

[0091] (3) Dehydration and drying

[0092] Li5Al3Ca3(SiO3) obtained in step (2) 10 After being placed in an oven at 105°C and dried for 8 h, the obtained product was in powder form and could not form a thin-sheet inorganic solid electrolyte.

[0093] Comparative Example 3

[0094] This comparative example uses commercial lithium aluminum titanium phosphate (LATP) solid electrolyte sheets available on the market for comparison. The solid electrolyte sheets were purchased from Clude New Energy Technology Co., Ltd. and have a chemical formula of Li 1.4 Al 0.4 Ti 1.6 (PO4)3, particle size 300 nm, calcination temperature 800℃, thickness 100 μm, bulk density 2.90 g / cm 3 .

[0095] Effect Example

[0096] The performance of various inorganic solid electrolytes prepared in Examples 1-4 and Comparative Examples 1-3 was compared, and they were respectively assembled into lithium metal all-solid-state batteries with 0.5 mm thick lithium sheets as negative electrodes and LiFePO4 as positive electrodes for various electrochemical performance tests. Among them, the elemental composition (molecular formula) was tested by inductively coupled plasma mass spectrometry; the thickness and density were tested in accordance with GB / T20220-2006; the conductivity and interface resistance were tested by AC impedance method (reference: Nanoporous regenerated cellulose separator for high-performance lithium ion batteries prepared by nonsolvent-induced phase separation. ACS Sustain ChemEng 2021, 9(44): 14756-14765.); the first discharge capacity and 100 cycle discharge capacity were tested in accordance with GB / T31467.2-2015. All tests were repeated three times. The results are shown in Table 1 below.

[0097] The lithium aluminum calcium silicon type inorganic solid electrolyte (Li 10 Al 1.33 Ca3(SiO3) 10 ) and the commercial lithium aluminum titanate phosphate Li in Comparative Example 3 1.4 Al 0.4 Ti 1.6 The results of the bulk resistance test and ionic conductivity test of (PO4)3 are as follows Figure 3 The interface resistance test results are shown in Figure 4 As shown; Li 10 Al 1.33 Ca3(SiO3) 10 The X-ray diffraction pattern is as follows Figure 5 shown.

[0098] Table 1 Comparison of performance of various inorganic solid electrolytes in the examples and comparative examples

[0099]

[0100] Through experimental comparison, it is proved that the inorganic solid electrolyte formed by the hydrothermal method prepared by the present invention has excellent ionic conductivity and electrochemical properties at room temperature. The raw materials of the lithium aluminum calcium silicon type inorganic solid electrolyte prepared by the present invention are low in price, the preparation process is simple and environmentally friendly, and the simultaneous formation of electrolyte synthesis and thin sheets is realized, and it has good application potential. Examples 1-4 and Comparative Examples 1-2 prove that the molar ratio range of various atoms described in the present invention is a prerequisite for realizing the synthesis of inorganic solid electrolytes and the simultaneous formation of thin sheets. Under the molar ratio described in the present invention, as the lithium atom content in the solid electrolyte increases, the ionic conductivity, interface resistance and volume resistance of the solid electrolyte can be effectively improved, which is then reflected in the macroscopic improvement of the battery cycle performance. Comparing Examples 1-4 with Comparative Example 2 proves that the performance of the lithium aluminum calcium silicon type inorganic solid electrolyte in the present invention is better than that of the commercial lithium aluminum titanium phosphate (LATP) solid electrolyte.

[0101] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. An inorganic solid electrolyte, characterized in that: The inorganic solid electrolyte has the molecular formula Li x Al y Ca3(SiO3) 10 ; Among them, x is 8~11, and y is 1~2.

2. The method for preparing an inorganic solid electrolyte according to claim 1, characterized in that: The steps include: (1) Raw materials ball milling and mixing The inorganic compound containing lithium, aluminum, calcium and silicon elements is mixed with water and then transferred to a ball mill for ball milling to obtain a paste required for hydrothermal reaction; (2) Hydrothermal forming The paste obtained in step (1) is transferred to a flat-bottomed mold, so that the paste is evenly spread horizontally in the mold, and then placed in a saturated steam environment at 150°C to 190°C for hydrothermal synthesis and simultaneous forming of thin sheets to obtain lithium aluminum calcium silicon type inorganic solid electrolyte thin sheets Li x Al y Ca3(SiO3) 10 ; Wherein, x is 8 to 11, and y is 1 to 2; (3) Dehydration and drying The lithium aluminum calcium silicon inorganic solid electrolyte sheet Li x Al y Ca3(SiO3) 10 The inorganic solid electrolyte is obtained by drying.

3. The method according to claim 2, characterized in that: The molar ratio of lithium, aluminum, calcium and silicon atoms in the paste described in step (1) is 8 to 11:1 to 2:3:

10.

4. The method according to claim 2, characterized in that: The inorganic compound containing lithium element described in step (1) is lithium hydroxide; The inorganic compound containing aluminum element in step (1) is at least one of aluminum oxide and aluminum hydroxide; The inorganic compound containing calcium element in step (1) is at least one of calcium oxide and calcium hydroxide; The inorganic compound containing silicon element described in step (1) is silicon dioxide.

5. The method according to claim 2, characterized in that: The mass ratio of the total mass of the inorganic compound containing lithium, aluminum, calcium and silicon elements described in step (1) to water is 1:6-9; The ball mill described in step (1) is a high-energy ball mill, the ball-to-material absolute dry mass ratio is 4:1, the ball milling speed is 600-700 rpm, and the ball milling time is 12-18 h.

6. The method according to claim 2, characterized in that: The particle size of the paste in step (1) is ≤200 nm; The crystal form of the lithium aluminum calcium silicon inorganic solid electrolyte sheet described in step (2) is garnet type, and the bulk density is 2.10-2.15 g / cm 3 ; Thickness is 50~100 μm.

7. The method according to claim 2, characterized in that: The time of the hydrothermal synthesis in step (2) is 12 to 24 hours; The drying conditions described in step (3) are: drying at 105±5°C for 5 to 10 hours.

8. Use of the inorganic solid electrolyte according to claim 1 in energy storage materials.

9. The use according to claim 8, characterized in that: The energy storage materials include energy storage materials used in electric vehicles, energy storage devices, and portable devices.

10. Use of the inorganic solid electrolyte according to claim 1 in preparing lithium metal solid-state batteries.

Citation Information

Patent Citations

  • Four-component iron co-doped garnet type solid electrolyte

    CN102780028A

  • Lithium-enriched anti-perovskite sulfides, solid electrolyte material containing lithium-enriched anti-perovskite sulfides and application of solid electrolyte material

    CN104466239A